Experimental and numerical investigation of the weld geometry effects on Type IV cracking behaviour in P91 steel - Mehmanparast, Ali; Yatomi, M.; Biglari, F.; Maleki, S.; Nikbin, K. (Elsevier, 2020)
The focus of the present study is on creep crack growth behaviour in Type IV region of P91 steel weldments at 650 °C. In the experimental studies on small- and large-scale single-edge notched specimens in tension, SENT, the effects of weld dimensions and specimen size on the creep crack growth behaviour of the material are investigated. The experimental results demonstrate that the crack starts to propagate at an angle normal to the loading direction, subsequently deviates towards the Type IV region and the specimen eventually ruptures when the crack growth angle becomes parallel to the loading direction. The creep rupture data for SENT specimens compared well with those of the round bar specimens for P91 welded joints. In addition, the data for crack growth rates from the deviating crack path were correlated with the C* fracture mechanics parameter and showed good agreement with standard compact tension test data. To predict the creep crack growth behaviour in the Type IV region, finite element simulations were performed in conjunction with a multiaxial ductility damage criterion at the weld/base metal interface. Given that a lower failure strain along the Type IV region is prominent, it is shown that the cracking, in line with the experiments, followed the HAZ region and led to the final creep rupture in the net section
Keywords: P91; High temperature failure; Large-scale testing; Creep crack growth; Type IV cracking